Perancangan Dan Pengembangan Alat Pengontrolan Interface Pengaman Listrik Peralatan Elektronik Rumah Tangga Berbasis Arduino - Derlini; Zulkarnain Lubis (Fakultas Teknik Universitas Samudra, 2020)
One cause of damage to electronic equipment is frequent blackouts. The reason is not because of the outage, but when the electricity is restored. This often happens because when the electricity is turned back on by the PLN, the voltage will be higher when it starts and after a while, it returns to normal. To overcome this problem a safety system can be made with a time delay. Based on an Arduino controller and voltage sensor, the system works to delay the time when the electricity starts. During the delay, the controller will read the PLN voltage. If the PLN voltage is still high then the delay will be extended until the voltage returns to normal. The voltage height limit is set at 235V through programming. The program was created in C language with the help of Avr 3.27 code vision software. The relay will be active if the voltage is normal so that the current can be channeled to the load. In addition to reading the voltage, the controller will also display the voltage read on an LCD display. Test results show the tool works with a fairly good response. A time delay of 5 seconds starts after the normal voltage which is below 235V. In addition to safety during blackouts, the system also works and protects if the voltage experiences fluctuations and exceeds 235V.